2000
DOI: 10.1073/pnas.220403797
|View full text |Cite
|
Sign up to set email alerts
|

Frataxin activates mitochondrial energy conversion and oxidative phosphorylation

Abstract: Friedreich's ataxia (FA) is an autosomal recessive disease caused by decreased expression of the mitochondrial protein frataxin. The biological function of frataxin is unclear. The homologue of frataxin in yeast, YFH1, is required for cellular respiration and was suggested to regulate mitochondrial iron homeostasis. Patients suffering from FA exhibit decreased ATP production in skeletal muscle. We now demonstrate that overexpression of frataxin in mammalian cells causes a Ca 2؉ -induced up-regulation of tricar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
165
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(172 citation statements)
references
References 59 publications
5
165
2
Order By: Relevance
“…33) Oxidative stress is caused by an imbalance in pro-oxidants and antioxidants, which cause a depletion or inactivation of the antioxidant in hepatocytes, ultimately leading to necrosis and/or apoptosis. 34,35) MDA is an indicator of oxidative stress and a major by-product resulting from lipid peroxidation. In addition, SOD, GSH-Px, GSH-Rd and catalase are the enzymes for which reduced activity is associated with the accumulation of reactive free radicals, leading to deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…33) Oxidative stress is caused by an imbalance in pro-oxidants and antioxidants, which cause a depletion or inactivation of the antioxidant in hepatocytes, ultimately leading to necrosis and/or apoptosis. 34,35) MDA is an indicator of oxidative stress and a major by-product resulting from lipid peroxidation. In addition, SOD, GSH-Px, GSH-Rd and catalase are the enzymes for which reduced activity is associated with the accumulation of reactive free radicals, leading to deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…Frataxin-deficient cells are impaired in oxidative phosphorylation (36), and there are several possible causes of this defect, including insufficient available inorganic phosphate.…”
Section: Physiological Implications Of Iron Accumulation and Precipitmentioning
confidence: 99%
“…Concurrently it was shown that frataxin promotes oxidative metabolism and ATP synthesis when overexpressed in fibroblasts (6), possibly by a direct interaction with the respiratory chain (7). Although the primary function of frataxin is still a matter of debate (8), some evidence suggests that this protein directs the intramitochondrial synthesis of Fe/S clusters (9 -12).…”
mentioning
confidence: 99%